2019
DOI: 10.1016/j.jjcc.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular noncompaction cardiomyopathy: Recent update on genetics, usefulness of biomarker, and speckle imaging

Abstract: Left ventricular noncompaction cardiomyopathy (LVNC) is an emerging form of predominantly genetically mediated cardiomyopathy characterized by failure of intrauterine compaction of the myocardium leading to the formation of two distinct layers of myocardium, an outer compacted thinner epicardial layer and an inner hypertrophied non compacted endocardial layer interspersed by blood-filled intertrabecular recess.We read with great interest the review article by Ikeda et al.[1] titled [ 1 8 _ T D $ D I F F ]`Isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Many studies have successfully identified genes associated with cardiomyopathy (118)(119)(120)(121)(122)(123)(124)(125), and this information can be employed in genome editing technology (126); while gene therapy will progressively develop in an increasing number of genetic tests, making the future eradication of LVNC promising, researchers are constantly refining genomic and proteomic analyses through animal models. These studies provide ideas for new therapeutic strategies in the future.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Many studies have successfully identified genes associated with cardiomyopathy (118)(119)(120)(121)(122)(123)(124)(125), and this information can be employed in genome editing technology (126); while gene therapy will progressively develop in an increasing number of genetic tests, making the future eradication of LVNC promising, researchers are constantly refining genomic and proteomic analyses through animal models. These studies provide ideas for new therapeutic strategies in the future.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%